Complementary Filter Optimal Tuning Methodology for Low-Cost Attitude and Heading Reference Systems with Statistical Analysis of Output Signal - Grzegorz Kopecki; Zbigniew A. Łagodowski (Applied Sciences)
Complementary filters are commonly used in low-cost AHRS systems. This article presents an algorithm for selecting the time constant of a complementary filter for AHRS systems. The AHRS and complementary filtering principles of operation are described, followed by a methodology for calibrating the filter. A simple method for acquiring calibration data is introduced, and these data are subsequently used in the proposed iterative algorithm for optimal time constant selection. The described method minimizes measurement errors and improves the accuracy of the system, ensuring operational stability. For the synthesis, data are recorded in a static position of the system at various pitch and roll angles. Next, the optimal time constant of the complementary filter is determined. The statistical properties of the attitude angles are then analyzed. The proposed methodology for system assessment and analysis is discussed.